Kajian Sosiologi Sastra: Bentuk Interaksi Sosial Antar Tokoh Dalam Novel Lebih Senyap Dari Bisikan Karya Andina Dwifatma - Rahayu Aprillia Erma; Dheni Harmaen; Rendy Triandy (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2023)
This research aims to analyze the form of social interaction between characters in the novel Lebih Senyap Dari Bisikan by Andina Dwifatma, and utilize the results of the analysis as an alternative teaching material for SMA class XII students. This research is a descriptive qualitative research whose analysis results will be described narratively. The data source in this analysis is the novel Lebih Senyap Dari Bisikan by Andina Dwifatma. The findings of the analysis show that this novel contains social interactions that are associative and dissociative. Associative social interaction consists of cooperation when the characters realize that they have the same interests, accommodation when the characters are willing to adjust to the new environment, and assimilation when the characters try to reduce differences. Meanwhile, dissociative social interactions consist of contravention when the characters cause disagreement with each other, and conflict when the characters oppose each other by hitting each other. The results of the analysis are then adjusted to the demands of the 2013 curriculum based on Core Competencies and Basic Competencies and made a product in the form of teaching materials to support the learning of SMA class XII students.